Adaptive changes of motoric status of preschool children under influence of physical education - Milenković Dejan A. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2018)
Adaptivity in physical exercise is the process of adjusting the body to the physical stimuli it is exposed to, which leads to changes in anthropological status. The aim of this research was to determine the adaptive changes in some of motoric abilities in physical education in pre-school children after three months of attending physical education. Twenty-five children of a pre-school age belonging to a senior educational group were tested. The initial testing was carried out at the beginning of the school year, and the second one was performed after three months of attending a pre-school institution. Eight motoric tests were applied: hand taping, leg taping, envelope test, figure '8' with bending, standing on one leg along the balance bar, standing on one leg with eyes closed, shooting the horizontal target with a ball, and squats. From statistical analysis, Student's T-test and discriminative analysis were used. The obtained results showed that, according to the observed multivariate level, there was an overall change of motoric status in preschoolers under the influence of physical education, while the individual level indicated non-existence of statistically significant differences in only one test. Thus, it can be concluded that the program of physical education produced the expected results.